Ethnic community in the time of urban branding. Issue 6 (1st November 2020) - Del Bono, Andrea
ABSTRACT: This article proposes to look at the Chinese community as a contextual assemblage rather than an epistemic truth in discussing urban multiculturalism in the Sydney urban context. In doing so, it steers clear from the 'groupist' analytical framework for the study of ethnicity, and it rejects paradigms such as 'the community' as a collective distinguished by 'a unique culture, held together by communitarian solidarity, and bound by shared identity'. A nuanced account of how the Chinese community becomes part of a system of value production is given, where acts of 'consensus' and 'alignment' are mobilised to embed its precarious formation within the branding strategies that aim to construct an ambiguous multi-Asian character for the precinct of Haymarket/Chinatown in the City of Sydney. These strategic positionings displace ethnicity understood as an essence, and the community as a taken for granted form of collective identification.